CREATING SPACE FOR GROWTH: FOSTERING CULTURAL AND ENVIRONMENTAL SUSTAINABILITY IN URBAN DEVELOPMENT - Awaliyah, Dian (Jurnal Pendekar Nusantara, 2023)
As cities continue to expand and evolve, the quest for additional space becomes inevitable. However, the conventional approach to urban development often involves displacing existing cultures and disrupting the natural environment, leading to social dislocation and ecological degradation. This paper explores innovative strategies for creating space within urban landscapes without the displacement of existing cultures and the destruction of fragile ecosystems. Drawing from multidisciplinary research in urban planning, architecture, sociology, and environmental science, this study examines the potential for sustainable urban development that respects the cultural and environmental heritage of a place. We analyze case studies from around the world where communities have successfully integrated growth while preserving their cultural identity and safeguarding the natural surroundings.. Through a comprehensive analysis of these principles and their implementation in diverse urban contexts, this paper advocates for a more holistic approach to urban development that prioritizes cultural preservation and environmental sustainability. By promoting strategies that create space while respecting existing cultures and environments, we can pave the way for more inclusive, resilient, and harmonious cities in the 21st century.